Women's Cancers: Pathways to Healing A Patient's Guide to Dealing with Ovarian and Breast Cancer - Del Priore, Giuseppe; Smith, J. Richard (Springer London : Imprint: Springer, 2009)
Women's Cancers: Pathway to Healing - A Patient's Guide to Dealing Ovarian and Breast Cancer provides accurate information that combines both orthodox medical treatments, along with more complementary and esoteric therapies. Giving not only a valuable source of information and support to women with cancer, it also proves a useful resource for families and friends; helping them to understand the process of management and treatment. The book incorporates a useful and novel '4-cusp approach,' which has proved very helpful to many women, both to themselves and also in allowing them to explain to their families where they are in the process. The '4-cusp approach' is like a map for people with cancer. Covering not only the medical, but also the emotional and psychological aspects of dealing with cancer, Pathways to Healing: A Patient's Guide to Ovarian and Breast Cancer aims to help anyone struggling to come to terms with their own, or a loved one's grief. Richard Smith, MD, FRCOG, Consultant Gynecological Surgeon at Chelsea and Westminster Hospital and Honorary Gynecologist at Royal Brompton Hospital, UK amongst many others. Dr Giuseppe Del Priore, Gynecologist specialising in cancer treatment. He works at New York University School of Medicine in New York City, USA and has a long standing interest in doctor-patient communication. He has been a pioneer in the field of fertility sparing surgery. .